Gamabufotalin Inhibits Osteoclastgenesis and Counteracts Estrogen-Deficient Bone Loss in Mice by Suppressing RANKL-Induced NF-κB and ERK/MAPK Pathways - Sun, Kaiqiang; Zhu, Jian; Deng, Yi; Xu, Ximing; Kong, Fanqi; Sun, Xiaofei; Huan, Le; Ren, Changzhen; Sun, Jingchuan; Shi, Jiangang (Frontiers in Pharmacology, 2021)
Osteolytic bone disease is a condition of imbalanced bone homeostasis, characterized mainly by excessive bone-resorptive activity, which could predispose these populations, such as the old and postmenopausal women, to developing high risk of skeletal fragility and fracture. The nature of bone homeostasis is the coordination between the osteoblasts (OBs) and osteoclasts (OCs). Abnormal activation of osteoclasts (OCs) could compromise the bone homeostasis, constantly followed by a clutch of osteolytic diseases, including postmenopausal osteoporosis, osteoarthritis, and rheumatoid arthritis. Thus, it is imperatively urgent to explore effective medical interventions for patients. The traditional Chinese medicine (TCM) gamabufotalin (CS-6) is a newly identified natural product from Chansu and has been utilized for oncologic therapies owing to its good clinical efficacy with less adverse events. Previous study suggested that CS-6 could be a novel anti-osteoporotic agent. Nevertheless, whether CS-6 suppresses RANK-(receptor activator of nuclear factor-κ B ligand)/TRAF6 (TNF receptor-associated factor 6)-mediated downstream signaling activation in OCs, as well as the effects of CS-6 on OC differentiation in vivo, remains elusive. Therefore, in this present study, we aimed to explore the biological effects of CS-6 on osteoclastogenesis and RANKL-induced activation of related signaling pathways, and further to examine the potential therapeutic application in estrogen-deficient bone loss in the mice model. The results of in vitro experiment showed that CS-6 can inhibit RANKL-induced OC formation and the ability of bone resorption in a dose-dependent manner at both the early and late stages of osteoclastogenesis. The gene expression of OC-related key genes such as tartrate-resistant acid phosphatase (TRAP), CTSK, DC-STAMP, MMP9, and β3 integrin was evidently reduced. In addition, CS-6 could mitigate the systemic estrogen-dependent bone loss and pro-inframammary cytokines in mice in vivo. The molecular mechanism analysis suggested that CS-6 can suppress RANKL/TRAF6-induced early activation of NF-κB and ERK/MAPK signaling pathways, which consequently suppressed the transcription activity of c-Fos and NFATc1. Taken together, this present study provided ample evidence that CS-6 has the promise to become a therapeutic candidate in treating osteolytic conditions mediated by elevated OC formation and bone resorption.